Effect of Occupational Safety and Health (K3) and Work Motivation on Employee Performance at Rumah Batik Tulis Al-Huda Sidoarjo - Akbar, Mochamad Andre Prawira; Kustini, Kustini (Budapest International Research and Critics University, 2021)
This research aims to find out the effect of Occupational Safety and Health (K3) and Work Motivation on Employee Performance at Rumah Batik Tulis Al-Huda Sidoarjo. This research uses a quantitative method with a saturated sample technique of 55 respondents. The analysis technique used in SMART PLS. The results showed that K3 and work motivation had a positive and significant impact on employee performance at Rumah Batik Tulis Al-Huda Sidoarjo.